Design of a Lower Limb Prosthesis for Ballet Practice - Blanca Monge Pérez; Cristina Alía García; Juan David Cano-Moreno (Applied Sciences)
Ballet is a discipline that combines art and sport in a harmonious way. It is a practice that has high physical and mental demands to achieve the proper body precision. During this activity, numerous muscles, including those in the legs, need to be exercised. Therefore, individuals who have lost part of their lower limb due to amputation face numerous significant challenges when it comes to practicing ballet. Throughout this article, the key aspects that influence the design of a lower limb prosthesis specifically adapted for ballet practice will be analyzed. New materials will be explored with the goal of designing an optimal model that ensures maximum performance and comfort for the users. Additionally, the prosthesis will be customized using 3D-printing technology, and a prototype will be presented. This study will merge biomechanics, ergonomics, and design. Its goal is to find a solution that improves the quality of life for lower limb amputees whose passion is ballet. The aim is to overcome physical and emotional barriers and provide a way to reintegrate amputee dancers into the world of dance. It is important to highlight the novelty of this work: combining different disciplines to provide a solution for individuals who engage in dance as a hobby rather than professionally. The proposed methodology aims to enable users with disabilities to access a personalized, complex, and potentially costly product.